Literasi Kesehatan Mental dan Perilaku Diagnosis Diri pada Mahasiswa - Putri, Cindi Maelani Putri Maelani; Aristi, Dela; Alkaff, Raihana Nadra; Desita, Uray Kania; Meilani, Henny; Sabrina, Salsabila; Maulidia, Rani Dwi Jayanti (UI Scholars Hub, 2025)
Background. College students must have mental health literacy in order to validate information about mental health and avoid self-diagnosis. Students will be better able to manage their mental health as their health literacy abilities improve. Aim. This research aims to understand the overview of mental health literacy and self-diagnosis behavior among college students at UIN Syarif Hidayatullah Jakarta. Method. This descriptive-analytical study employs a cross-sectional strategy. The convenience sampling approach was used to pick a sample of 409 college students from UIN Syarif Hidayatullah Jakarta. Result. According to the findings, 24.2% of respondents lacked mental health literacy. As many as 54% of respondents engaged in self-diagnosis activity related to mental health, with the internet/social media being the most common source of knowledge. According to the cross-tabulation results, respondents with moderate and high mental health literacy engaged in self-diagnosis behavior at rates of 62.1% and 53.2%. College students with strong mental health literacy (moderate to high) are more likely to participate in self-diagnosis behavior. College students are expected to be able to discover trustworthy sources of mental health information online. The university can develop campaigns, screening programs, and a mental health literacy curriculum.